2018
DOI: 10.1016/j.nut.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Time-course changes in circulating branched-chain amino acid levels and metabolism in obese Yucatan minipig

Abstract: A B S T R A C TObjectives: High-fat high-sucrose diet (HFHS) overfeeding is one of the main factors responsible for the increased prevalence of metabolic disorders. Elevated levels of branched-chain amino acids (BCAAs) have been associated with metabolic dysfunctions, including insulin resistance (IR). The aim of this study was to elucidate whether elevated BCAA levels are the cause or the consequence of IR and to determine the mechanisms and tissues involved in such a phenotype. Methods: We performed a 2-mo f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 26 publications
1
28
1
Order By: Relevance
“…Interestingly, the increased transamination potential during the first weeks of HFHS feeding could be the consequence of a metabolic adaptation to the progressively increase in BCAA levels. However, by the end of the trial, the potential to catabolise BCAA was blunted, in agreement with a defective oxidative deamination observed in the adipose tissue of HFHS-fed minipigs [ 25 ].…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Interestingly, the increased transamination potential during the first weeks of HFHS feeding could be the consequence of a metabolic adaptation to the progressively increase in BCAA levels. However, by the end of the trial, the potential to catabolise BCAA was blunted, in agreement with a defective oxidative deamination observed in the adipose tissue of HFHS-fed minipigs [ 25 ].…”
Section: Discussionmentioning
confidence: 60%
“…BCAA related-enzyme activities and mRNA levels were also reduced by the end of the trial, supporting the idea of a progressively reduction of BCAA catabolism from obese minipigs. We and other have shown that in obese and insulin resistant animal models, BCAA circulating levels increased with time [ 25 , 43 ]. Interestingly, the increased transamination potential during the first weeks of HFHS feeding could be the consequence of a metabolic adaptation to the progressively increase in BCAA levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is as yet unclear at which stage during overfeeding these adaptive processes can be regarded as part of normal metabolic flexibility or whether they reflects negative side effects in the spectrum of the metabolic syndrome [ 2 ]. Thus, we have recently shown that in mini-pigs overfed with a high fat–high sucrose (HFHS) diet for two months, major modifications in the postprandial metabolism occur after only one week of feeding [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%